An Investigation into the Effectiveness of Green Betel (Piper betle L.) Leaf Extract Hand Sanitizer - Yahya, Diyas Aledya; Permatasari, Intan; Ma'mun, Sholeh (BERKALA SAINSTEK, 2023)
Green betel (Piper betle L.) leaf contains anti-thrush, anti-cough, astringent, and antiseptic chemicals such as saponins, flavonoids, polyphenols, and essential oils. Hand sanitizer can also be used as an antiseptic agent, which is a more practical option. The purpose of this study was to see how the composition of green betel leaf extract made by infusion affected its physical properties and bacterial inhibition. Hand sanitizer samples were made using different concentrations of green betel leaf extract (10 - 25 wt%) with and without the addition of tea tree essential oil. Sample testing included organoleptic tests, physical properties tests, and effectiveness tests on the growth of Escherichia coli bacteria. The results showed that the best composition was found to be at a concentration of 10 wt% green betel leaf extract without the addition of essential oil, with pH ranging from 5.2 to 5.8 and viscosities ranging from 1.32 to 1.99 cps, in the form of a watery gel and a clear yellow color. Meanwhile, hand sanitizer sensitivity testing revealed that none of the samples could inhibit the growth of Escherichia coli bacteria. This indicates that the concentration of green betel leaf extract in the sample is still insufficient to inhibit bacterial growth.